PEMBENTUKAN PERSONAL BRANDING @jharnabhagwani SEBAGAI BEAUTY INFLUENCER MELALUI TIKTOK - Nur Fakih, Farah Isabella; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
Personal branding is explained as a communication strategy about a person's characteristics that can lead people to sympathize or support them. Personal branding can be found on social media, especially TikTok. Jharna Bhagwani is a young girl of Indian-Indonesian blood who is pouring her hobby into makeup. The results of the makeup content are dominantly containing tips, tricks, point of view (stories/roles), and daily makeup. This study aims to determine the formation of Jharna Bhagwani's personal branding as a beauty influencer through TikTok. This research is a descriptive qualitative research on personal branding theory by Montoya, namely the 8 laws of personal branding and semiotic analysis by Peirce. The results of this study that Jharna is a beauty influencer who displays the implied meaning of most of her makeup videos. Her makeup content has also succeeded in bringing her achievements, "Best of Fashion & Beauty" at TikTok Award Indonesia 2020. Keywords: personal branding, Jharna Bhagwani, beauty influencer, TikTok